A kind of polyetheresteramide antistatic agent and preparation method thereof
By adding zinc oxide and polyglycidyl ether polymer to the polyether ester amide antistatic agent and performing tensile orientation preparation, the problem that antistatic agents are difficult to have high hardness and high antistatic properties is solved, and the mechanical strength and antistatic properties are significantly improved.
Patent Information
- Application Number
- CN202411250460.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-09-06
AI Technical Summary
Polyetherestamide antistatic agents are difficult to have high hardness and high antistatic properties. In the prior art, the improvement of antistatic properties will lead to a decrease in mechanical strength and vice versa.
When preparing polyether ester amide antistatic agent, zinc oxide and polyglycidyl ether polymer are added to form zinc salts through zinc oxide to improve antistatic properties, and the polyglycidyl ether polymer is reacted with the polyamide hard and polyether soft segments to introduce a crosslinking network to improve mechanical strength. Meanwhile, a multi-porous sheet-like structure is prepared by performing tensile orientation before granulation to further improve the antistatic properties.
The high hardness and high antistatic properties of polyether ester amide antistatic agents have been achieved, and the mechanical strength and antistatic properties have been significantly improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of antistatic agents, and in particular to a polyetheresteramide antistatic agent and a preparation method thereof. Background Art
[0002] Polymer materials have the characteristics of light weight, wear resistance, corrosion resistance, excellent mechanical properties, and easy processing. Their market share will be higher and higher in the future. However, most polymer materials are electrical insulating materials with relatively high resistivity. They are easy to accumulate charges during their processing or product use, which is difficult to remove. The accumulation of a large amount of charges can easily cause adverse effects. Once static electricity is generated in polymer materials or finished products, it will not only have an adverse effect on the processing and performance of the materials, the use and appearance of the products, but also pose a great safety hazard in some special industries. For example, the accumulation of a large amount of static electricity in industries such as petroleum, chemical, coal mining, and underground space operations can lead to fires and even explosions.
[0003] In particular, for a large number of special applications, the material must have high hardness and high wear resistance, but it must also prevent the generation and accumulation of static electricity during the friction process to avoid unexpected safety risks. Therefore, the added antistatic agent needs to have good hardness and antistatic properties. In these applications, graphene and metal-based conductive fillers can play a good reinforcing and antistatic effect, but these conductive fillers usually have problems such as uneven filler distribution, easy precipitation, and color deterioration. The antistatic effect is short-lived and it is easy to generate static safety risks in the later stage, which is an unacceptable disadvantage.
[0004] Based on the theory of organic polymer solid electrolytes, some researchers use the coordination complexation of polyether substances and inorganic salts to prepare polymer permanent antistatic agents. When the polymer antistatic agent and the polymer matrix material are blended, the polymer antistatic agent is distributed in fine layers or tendons on the surface of the product to form a conductive surface layer, and an interpenetrating network is formed in the center to form a body conductive path.
[0005] Polyetheresteramide antistatic agent is an innovative product in the field of polymer material technology, mainly used to solve the static electricity problem caused by friction, collision or electrostatic induction in polymer materials in industrial production and daily life. This type of antistatic agent has excellent charge dissipation and can be blended with polymer matrix materials to form a conductive surface layer and interpenetrating network, thereby effectively preventing the generation and accumulation of static charge. Due to its excellent antistatic performance and little effect on substrate performance, polyetheresteramide antistatic agent has broad application prospects in electronic equipment packaging, precision instruments, semiconductor chips and other fields. With the continuous advancement of preparation technology, the application scope of this type of antistatic agent is expected to be further expanded.
[0006] However, as a polymer material, although polyetheresteramide antistatic agent has good inherent mechanical properties, it still has the problem of difficulty in achieving both high hardness and high antistatic performance. This is because the antistatic performance of polyetheresteramide mainly comes from the ether bonds on the polyether soft segment. A large number of ether bonds can combine with moisture in the air to accelerate charge dissipation. Therefore, in order to obtain higher antistatic performance, it is necessary to increase the proportion of polyether soft segment, which will inevitably lead to a decrease in its strength, and vice versa. Therefore, obtaining a polyetheresteramide antistatic agent with both high hardness and high antistatic performance is a technical problem that needs to be solved urgently but is difficult to solve. Summary of the invention
[0007] In order to improve the problem that conventional polyetheresteramides are difficult to have both high hardness and high antistatic performance, the present application provides a polyetheresteramide antistatic agent and a preparation method thereof.
[0008] The present application provides a polyetheresteramide antistatic agent and a preparation method thereof using the following technical scheme:
[0009] In the first aspect, the present application provides a polyetheresteramide antistatic agent, which adopts the following technical solution:
[0010] A polyetheresteramide antistatic agent, the antistatic agent having a polyamide hard segment and a polyether soft segment, the raw materials for preparing the antistatic agent comprising zinc oxide and a polyglycidyl ether polymer, the polyglycidyl ether polymer being one of polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, glycerol triglycidyl ether or a mixture of at least two thereof;
[0011] The antistatic agent is in a flake shape and has a microporous structure. The antistatic agent is stretched and oriented before being granulated.
[0012] By adopting the above technical scheme, polyetheresteramide is a thermoplastic elastomer material, which is generally produced by a condensation reaction of a polyamide containing a dihydroxy group and a polyether diol in a molten state, or by an esterification reaction of a polyamide containing a dicarboxyl group and a polyether diol in a molten state. The polyether component is embedded in the linear chain part of the polyamide, so it has the two properties of hardness of polyamide (PA) material and softness of polyether (PE) material.
[0013] In its molecular chain, the polyamide hard segment has a high degree of crystallinity and thus a high hardness due to the presence of a large number of strong hydrogen bonding forces. At the same time, the hard segment serves as a physical crosslinking point; while the polyether soft segment has good flexibility and can undergo large deformation. This block molecular chain structure of alternating soft and hard segments constitutes a three-dimensional network. It is generally believed that by controlling the hard segment and the soft segment and their ratio, elastomer specifications with different flexibility and different hardness can be obtained without adding any plasticizer. This view is not wrong. As the proportion of the hard segment increases, the mechanical strength of the antistatic agent tends to increase accordingly. However, the antistatic property of polyether ester amide comes from its polyether soft segment. The ether bond in the soft segment itself has a charge transfer effect, and the hydrophilic ether bond can form a conductive water film to effectively absorb and disperse static electricity and reduce static electricity accumulation. Therefore, although the increase in the proportion of the hard segment can indeed bring about an increase in mechanical strength, it often also brings about a decrease in its antistatic performance. It is difficult to have both.
[0014] Based on the above problems, the present application specifically adds zinc oxide and polyglycidyl ether polymer when preparing polyetheresteramide, wherein zinc oxide can form zinc salt during the reaction, and the ionic conductivity and tunnel effect of the zinc salt can accelerate the dissipation of charges and improve the antistatic performance.
[0015] In addition, the epoxy groups in the specifically added polyglycidyl ether polymer react with the electrophilic groups (such as hydroxyl, amine, carboxyl) in other compounds to open the ring. Therefore, whether it is the carboxyl or hydroxyl groups carried by the polyamide hard segment or the hydroxyl groups carried by the polyether segment, they can react with the polyglycidyl ether polymer. Among them, the carbonyl carbon in the carboxyl group has a certain electrophilicity and can attack the epoxy group, causing the epoxy group to open the ring, and the hydroxyl group attacks the carboxyl carbon again, thereby reacting. It is generally believed that the carboxyl group and the epoxy group will first undergo an esterification reaction when the ring is opened, thereby generating a hydroxy ester; similarly, the reaction of the hydroxyl group and the epoxy group is that the epoxy opens the ring and forms a hydroxy ether with the hydroxyl group. Therefore, whether the polyglycidyl ether polymer reacts with the carboxyl / hydroxyl group of the hard segment or the hydroxyl group of the soft segment, a hydrophilic hydroxyl group will be introduced. Therefore, polyglycidyl ether actually plays a role similar to that of a cross-linking agent. The active groups at both ends react with the polyamide hard segment or the polyether segment respectively, which can not only connect the polyether segments to each other, but also connect the polyether segments to the end groups of the polyamide hard segment. In addition, during the reaction, since the hydrophilic hydroxyl groups are reintroduced, the hydrophilic properties will not be significantly reduced due to the reaction of the hydrophilic carboxyl or hydroxyl groups.
[0016] It is particularly important to note that the heat resistance of the polyether soft segment is relatively poor, and it is difficult to avoid the rupture of the ether bond during the reaction, thereby introducing a large number of hydroxyl groups. Such ether bond rupture generally leads to a decrease in the crystallinity and molecular chain regularity of the soft segment, thereby leading to a decrease in the mechanical strength of the antistatic agent, so the ether bond rupture is generally undesirable. However, since the polyglycidyl ether polymer is specifically added in the present application, the hydroxyl group introduced by the ether bond rupture will instead become a reaction site with the polyglycidyl ether polymer. One end of the polyglycidyl ether polymer reacts with the hydroxyl group introduced by the ether bond rupture, and the other end reacts with the active group on the polyamide hard segment or with the hydroxyl group on the remaining polyether soft segment, thereby introducing a relatively complex cross-linking network in the polyether soft segment to obtain good mechanical strength. Moreover, this reaction process does not "consume" ether bonds or hydrophilic groups such as hydroxyl and carboxyl groups. Instead, after reacting with a hydrophilic group, a hydroxyl hydrophilic group is reintroduced. This means that the increase in the strength of the polyether soft segment does not lead to a decrease in its hydrophilic conductivity. The cross-linked network structure of the soft segment cooperates with the ions of the zinc salt to form a more complete conductive network, which makes the improvement of the mechanical strength of the antistatic agent accompanied by the improvement of the antistatic performance, which is a very unexpected result.
[0017] It is particularly important to note that the amide group (imino group) in the polyetheresteramide has low reactivity. Therefore, under the conditions of the present application, the polyglycidyl ether is more inclined to react with the active groups of the polyether segment and with the active end groups of the polyamide hard segment. Therefore, the effect of the polyglycidyl ether on the polyamide hard segment is only to react with its active end groups, without affecting the crystallization of the polyamide hard segment itself. Therefore, for the antistatic agent, its hard segment is almost unaffected, while the strength and antistatic properties of the soft segment are improved, which ultimately makes the antistatic agent have both high strength and good antistatic properties.
[0018] In summary, the introduction of polyglycidyl ether polymer has little effect on the hard segment of polyamide, but can significantly improve the mechanical strength of the soft segment. The conductive network formed in the soft segment cooperates with the evenly distributed zinc salt ions to form a significantly more complete conductive network with significantly good antistatic properties. Therefore, the antistatic agent exhibits unexpectedly high strength and high antistatic properties.
[0019] Further, the antistatic agent in the present application is not prepared into conventional olive-shaped, long granular, spherical and other conventional shapes, nor is it prepared into a more common dense non-porous structure, but is prepared into a special multi-microporous sheet structure by stretching orientation before granulation. This operation actually reduces the mechanical strength of the antistatic agent itself (introducing pores, inevitably leading to a decrease in strength). It is generally believed that the decrease in the mechanical strength of the antistatic agent often leads to a decrease in the strength of the blended material. However, the inventors of the present application have found that this low-strength special structure antistatic agent can make the blended material (such as PA66) have higher mechanical strength and antistatic properties. And by reducing the mechanical strength of the antistatic agent, the mechanical strength of the blended material can be improved, which is a very unexpected result.
[0020] This may be because, on the one hand, the stretching treatment can significantly improve the orientation of the molecular chain in the preparation process of the antistatic agent, thereby reducing the entanglement of the molecular chain, and the stretching process makes it easier to produce microporous structures at the soft segment because of the different deformation capabilities of the hard segment and the soft segment. Regardless of the low entanglement, high orientation of the molecular chain, or the introduced microporous structure, the molecular chain structure of the antistatic agent can be more easily disentangled and evenly dispersed after the antistatic agent is blended with the material (molecular chains with high orientation have low entanglement and are better disentangled; the presence of micropores improves the heat transfer channel during the mixing and melting, so that the heating is more uniform, and on the other hand, the presence of micropores provides a "breakthrough" for disentanglement), which greatly reduces the possibility of a large number of entanglements of the antistatic agent molecular chain and the introduction of defects due to compatibility issues with the material; in addition, the molecular chain of the antistatic agent with high orientation is easier to present a fibrous distribution in the material, and the molecular chain with a fibrous distribution is obviously easier to form a three-dimensional conductive network interconnected in the material, thereby obtaining a better antistatic effect.
[0021] It should be noted that although the polyetheresteramide antistatic agent has good compatibility with most materials, the presence of the polyether soft segment leads to inevitable compatibility problems. It is still easy to produce stress concentration, which leads to a decrease in material strength after adding the antistatic agent (for example, the mechanical strength of pure PA66 is greater than the mechanical strength of PA66 after adding the antistatic agent). The well-disentangled molecular chains significantly reduce the possibility of stress concentration.
[0022] Optionally, the porosity of the antistatic agent is 10-30%, and the Shore hardness of the antistatic agent is 40-80D.
[0023] By adopting the above technical scheme, on the basis of unchanged composition, the higher the porosity of the antistatic agent, the lower its hardness (mechanical strength to a certain extent). Porosity is not too low, hardness is not too high, which means that during stretching treatment, part of the polyether soft segment is pulled open into holes, and at this time, the molecular chain produces a relatively sufficient orientation to ensure that the entanglement degree of the antistatic agent molecular chain is low, on the one hand, it is ensured that there is good disentanglement dispersibility after mixing with the material to improve mechanical strength, and on the other hand, the highly oriented molecular chain is more likely to form an interconnected conductive network after dispersion to improve antistatic ability. Of course, the porosity of the antistatic agent should not be too high, and the hardness should not be too low. Too high porosity often means overstretching, which will have an adverse effect on the regularity of the polyamide hard segment, and the orientation degree of the molecular chain decreases, so as to cause lower mechanical strength and antistatic performance after blending with the material.
[0024] Optionally, the surface of the antistatic agent has stretching holes, the stretching holes are in the shape of long strips, the long diameter of the stretching holes is 2-4 times the short diameter, and the Shore hardness of the antistatic agent is 50-70D.
[0025] By adopting the above technical solution, since the strength of the hard segment with high crystallinity is significantly greater than that of the soft segment, the soft segment is more likely to absorb strain energy and deform or even separate during the stretching process, thereby forming a stretched hole structure on the surface of the antistatic agent. And since the stretching force is directional during the stretching process, the hole often first produces cracks, then expands to form a long strip (ellipse-like), and continues to stretch to form a circular hole. The inventors of this application found that when the shape of the stretched hole is a long strip (ellipse-like) and the ratio of the major diameter to the minor diameter is 2-4, the antistatic agent can obtain better comprehensive mechanical strength and antistatic performance after blending with the material.
[0026] It is particularly important to note that, quite unexpectedly, the increase in the size of the pore structure leads to a decrease in the strength of the antistatic agent (such as from 80D to 70D), which can make the blended material have higher mechanical strength. This result that adding a low-strength antistatic agent can make the blended material have higher strength is inconsistent with conventional cognition. This may be because, as the stretching proceeds, although the porosity increases, the pore size increases, and the hardness of the antistatic agent decreases, the molecular chain orientation of the antistatic agent increases, and the difficulty of disentanglement decreases, which can make the final blended material have higher mechanical strength.
[0027] Optionally, the average major diameter of the stretching holes is 100-300 nm, and the area of the stretching holes accounts for 30-50%.
[0028] By adopting the above technical solution, the major diameter and area ratio of the stretching holes reflect the proportion of the soft segment on the one hand, and the degree of stretching on the other hand. The inventors of this application found that when the average major diameter of the stretching holes of the antistatic agent is 100-300nm and the area ratio of the stretching holes is 30-50%, the antistatic agent finally blended has a more preferred antistatic performance and mechanical strength.
[0029] It is understood that the so-called area ratio of the stretching holes refers to the area ratio of the stretching holes per unit area measured by microscopic characterization of the antistatic agent (such as shooting SEM), which is the area ratio of the stretching holes. This measurement process can be performed manually or automatically through software such as Image J. For example, in the field of view of the SEM image of 10μm×10μm, the total area of all the stretching holes is measured to be 100μm 2 , it is considered that the area of the stretched hole accounts for 10%.
[0030] In a second aspect, the present application provides a preparation process of a polyetheresteramide antistatic agent, which adopts the following technical solution:
[0031] A preparation process of a polyetheresteramide antistatic agent comprises the following process steps:
[0032] S1, preparation of zinc dicarboxylate, placing a dicarboxylic acid end-capping agent and zinc oxide in a reaction vessel, adding excess acetone as a solvent, reacting at a temperature of 30-40° C. for 40-60 minutes, filtering, washing, and drying to obtain zinc dicarboxylate salt;
[0033] S2, preparation of polyether ester, adding a polyether compound to the prepared zinc dicarboxylate, controlling the reaction temperature to 160-170° C., and the reaction time to 3-5 h, to obtain a polyether ester with zinc;
[0034] S3, prepolymer preparation, caprolactam and water are added to a reaction container, reacted in an inert gas atmosphere, the reaction temperature is 200-220°C, and the reaction degree is controlled to be no more than 700°C·h, to obtain a polycaprolactam prepolymer; preferably, the reaction degree is controlled to be 600-650°C·h;
[0035] S4, polymerization, mixing the polyether ester and polycaprolactam prepolymer prepared in step S2 and step S3, first reacting for 1-2 hours under an inert gas atmosphere at 210-230° C., then adding the polyglycidyl ether polymer, evacuating the mixture and heating the mixture to 255-265° C., and continuing the reaction for 2-3 hours to obtain a block polymer;
[0036] S5, extrusion granulation, mixing the block polymer obtained in step S4 with NMP to obtain a rubber material, extruding it onto a carrier, the speed of the carrier being greater than the extrusion speed of the rubber material, then drying and curing the rubber material on the carrier to obtain a rubber strip, stretching the rubber strip and pelletizing it to obtain a sheet-like antistatic agent with stretching holes distributed therein.
[0037] By adopting the above technical scheme, through step S1 and step S2, a polyether ester with zinc can be prepared, and the polyether ester, as a precursor of the polyether soft segment in the antistatic agent, greatly affects the mechanical strength and antistatic properties of the final antistatic agent. In step S2, by controlling the reaction temperature and reaction time, the degree of polymerization of the polyether ester can be adjusted. The higher the reaction temperature and the longer the time, the higher the degree of polymerization of the polyether ester. In the final antistatic agent, the molecular chain length of the single polyether soft segment is large but the distribution density decreases, and the high polymerization degree of the polyether ester segment has improved temperature resistance (based on mechanical strength considerations, this is generally expected to see), it is not easy to break the chain to introduce hydroxyl groups, and it is naturally not easy to react with polyglycidyl ether polymers, and whether it is in the form of long chain low distribution density or not easy to react with polyglycidyl ether polymers, it is not conducive to forming an interconnected three-dimensional conductive network. Therefore, it is necessary to control the reaction temperature in step S2 to be not higher than 170°C and the reaction time to be not more than 5h.
[0038] Correspondingly, in order to ensure that the polyether soft segment has basic strength, it is necessary to control the reaction temperature in step S2 to be not less than 160° C. and the reaction time to be not less than 4 h.
[0039] In step S3, the polycaprolactam prepolymer, as the precursor of the polyamide hard segment, largely determines the mechanical strength performance of the final antistatic agent. It is generally believed that in order to improve the mechanical strength of the antistatic agent, it is beneficial to increase the degree of polymerization of the polycaprolactam prepolymer. Of course, this often leads to a decrease in the antistatic performance of the antistatic agent. However, the inventors of the present application surprisingly found that by controlling the preparation process of the polycaprolactam prepolymer, in particular, on the basis of a reaction temperature of 200-220°C, controlling the reactivity to be no more than 700°C·h (the product of the reaction temperature and time) to adjust the polycaprolactam prepolymer to have a not too high degree of polymerization, the final antistatic agent can have better mechanical strength and antistatic performance.
[0040] This may be because, as the length and crystallinity of the polyamide hard segment molecular chain increase, the mechanical strength of the antistatic agent generally increases as the hard segment has a greater impact on the mechanical strength of the antistatic agent. However, this also means that the polyamide hard segment has a stronger pulling effect on the polyether soft segment, making it difficult for the polyether soft segment to be arranged regularly, resulting in a decrease in the mechanical strength of the polyether soft segment. In addition, the increase in the length of the polyamide hard segment molecular chain means that the distance between adjacent polyether soft segments is greatly increased, making it difficult to form an interconnected conductive network, and the antistatic performance decreases accordingly.
[0041] Therefore, based on the consideration of antistatic performance, the length of the polyamide hard segment molecular chain should be controlled, and the polyglycidyl ether polymer is specifically introduced in the present application, which can form a polyether soft segment with significantly higher mechanical strength by reacting with the active groups on the polyether soft segment and the polyamide hard segment; and the pulling effect of the polyamide hard segment with a lower molecular chain length on the polyether soft segment is reduced, which can also improve the strength of the polyether soft segment. Considering that the introduction of the polyglycidyl ether polymer can form a high-strength and conductive three-dimensional network structure through more active groups on the polyether soft segment, this covalently bonded three-dimensional structure has a higher bonding strength than the hydrogen bonds between polyamides. Various factors lead to controlling the reactivity of the polycaprolactam prepolymer to be no more than 700℃·h during preparation, which can make the mechanical strength and antistatic performance of the antistatic agent better.
[0042] In step S4, a preliminary reaction at a slightly low temperature and a high temperature reaction after adding the polyglycidyl ether polymer are used. With this two-step low temperature-high temperature reaction method, the low temperature reaction can ensure good reaction and chain formation between the hard segment and the soft segment, and the further high temperature reaction can ensure that some of the unreacted polyether monomers release hydroxyl groups, and through the reaction with the polyglycidyl ether polymer, a high-strength, high-conductivity three-dimensional network structure is introduced in the polyether soft segment region. It is particularly important to note that it is generally believed that the ether bond breakage in the polyether soft segment is undesirable because it will lead to a decrease in the strength of the soft segment, while in the present application, it is hoped that the ether bond in the polyether soft segment will produce a certain amount of hydroxyl groups because this can improve the strength and antistatic properties of the polyether soft segment. Of course, it should be noted that the low temperature reaction is also necessary to avoid excessive breakage of the ether bond in the polyether soft segment, making it difficult to form the desired polyether ester amide material.
[0043] In step S5, the block polymer is mixed with NMP before extrusion granulation to obtain a rubber material with significantly reduced viscosity, which can greatly improve the mobility of the block polymer in the rubber material. After the low-viscosity rubber material is applied to a carrier, the carrier with a faster running speed will stretch the uncured rubber material and spread it flat, thereby obtaining a sheet-like rubber material. Before the rubber material is dried and cured, this stretching force can increase the orientation of the molecular chain and partially pull apart the polyether soft segment to obtain an antistatic agent with a porous structure.
[0044] Optionally, in step S4, the mass ratio of polyether ester to polycaprolactam prepolymer is 0.2-0.3:1; and the added amount of the polyglycidyl ether polymer is 0.2-0.4 times the added amount of the polyether ester.
[0045] By adopting the above technical solution, the mass ratio between the polyether soft segment and the polyamide hard segment is controlled within a relatively reasonable range, so that the antistatic agent itself can have relatively reasonable basic performance. The addition amount of the polyglycidyl ether polymer is further controlled based on the addition amount of the polyether ester, on the one hand, to ensure that the hydroxyl groups released in step S4 can better react with the polyglycidyl ether polymer to improve the antistatic performance and mechanical strength, and on the other hand, considering that the polyglycidyl ether polymer also has compatibility problems with the material, it is necessary to control the addition amount of the polyglycidyl ether polymer not to be too large, so as to avoid introducing a large number of defects due to compatibility problems, resulting in a decrease in the mechanical strength of the final blended material.
[0046] Optionally, in step S1, the ratio of the amount of zinc oxide added to the amount of dicarboxylic acid end-capping agent added is controlled to be a molar ratio of 2.2-2.5:1; the dicarboxylic acid end-capping agent is selected from one of oxalic acid, adipic acid, sebacic acid, and suberic acid, or a mixture of at least two of them.
[0047] By adopting the above technical solution, it is generally believed that in order to make zinc oxide and dicarboxylic acid capping agent fully react, the molar ratio of the two should be controlled to be approximately 2:1, otherwise there will be a problem of excess zinc oxide. The role of zinc oxide is generally believed to be to improve the antistatic performance, but the addition of zinc oxide will affect the crystallization behavior and thus cause a decrease in hardness.
[0048] The inventors of the present application unexpectedly found that by controlling the molar ratio of zinc oxide to dicarboxylic acid end-capping agent, it is possible to ensure that zinc oxide is appropriately excessive, so that the antistatic agent not only has predictable better antistatic properties, but also has unexpected higher mechanical strength. This may be due to the fact that the hydroxyl groups on the surface of slightly excessive zinc oxide can hydrogen bond with the amide groups on polyamide, and since the polyamide hard segment is crystallized by hydrogen bonds, therefore, slightly excessive zinc oxide can slightly reduce the crystallinity of polyamide. And the excessive crystallinity of the hard segment means that it is regularly arranged by a larger amount of hydrogen bonds, which can cause the decline of its end group accessibility (the number of active free end groups decreases) on the one hand, and is not easy to react with polyglycidyl ether polymers, in addition, the excessive crystallinity of the hard segment can also pull the soft segment to cause its crystallization difficulty to further improve. Therefore, on the basis of the specific addition of glycidyl ether polymers, by controlling the slightly excessive zinc oxide to slightly reduce the crystallinity of the polyamide hard segment, it is possible to make the final obtained antistatic agent have higher mechanical strength and antistatic performance.
[0049] Optionally, in step S2, the molar ratio of zinc dicarboxylate to the polyether compound is 1:1.1-1.2; the polyether compound is one of polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol, or a mixture of at least two of them.
[0050] Optionally, step S5 specifically includes the following steps:
[0051] S51, extrusion, mixing the block polymer obtained in step S4 with NMP to obtain a rubber material, and controlling the solid content to be 10-15wt%, and controlling the temperature of the rubber material to be 80-100° C., and then extruding it onto a carrier, wherein the speed of the carrier is greater than the extrusion speed of the rubber material, and then drying and curing the rubber material on the carrier to obtain a rubber strip;
[0052] S52, stretching treatment, stretching the rubber strip by 1.5-2 times at 30-40°C, and then heat treating it at 70-90°C for 30-60min. After the heat treatment, cooling and pelletizing are performed to obtain a sheet-like antistatic agent with stretching holes distributed therein.
[0053] By adopting the above technical solution, the viscosity of the rubber can be adjusted by controlling the solid content and temperature of the rubber, thereby controlling the difficulty of the movement of the molecular chains therein. Therefore, by controlling the solid content of the rubber to be not higher than 15% and the temperature to be not lower than 80°C, it can be ensured that when subjected to a tensile force, the molecular chains in the rubber have sufficient mobility to facilitate orientation.
[0054] Further, by stretching at a lower temperature and heat treatment at a higher temperature, the final antistatic porous structure can be ensured. This is because, under slightly lower temperature conditions, the hard segment with high crystallinity has high hardness and is not easy to deform under stretching, while the soft segment with low crystallinity is more likely to deform or even break into pores, thereby introducing a pore structure in the antistatic. If the stretching temperature is too low, the hardness of the soft segment is also too high, making it difficult to form pores; if the stretching temperature is too high, the hardness of the hard segment decreases, and it is also easy to shift during stretching, and the stretching force is difficult to concentrate on the soft segment, so it is difficult for the soft segment to form the desired pore structure. Further heat treatment can eliminate the stress concentration caused by stretching and play a role in stabilizing the pore structure.
[0055] Optionally, in step S51, the distance between the rubber extrusion port and the carrier is 2-5 cm, the speed of the carrier is 2-3 times the rubber extrusion speed, and the drying temperature is 10-20° C. lower than the temperature of the rubber.
[0056] By adopting the above technical solution, the distance between the rubber material and the carrier after extrusion and the ratio of the carrier to the rubber material extrusion speed are controlled, which can ensure that the rubber material is subjected to a sufficiently large drafting force on the one hand, and on the other hand ensure that it has enough time for the molecular chain to be oriented by force, thereby improving the orientation degree of the molecular chain, laying a foundation for the formation of the required pore structure in the stretching process in the subsequent step S52. If the drying temperature is controlled not to be too high, the curing time of the rubber material is appropriately delayed, allowing the molecular chain to continue to be oriented under the action of residual stress.
[0057] It can be understood that the distance between the rubber extrusion port and the carrier refers to the shortest distance between the two, and is also the length that the rubber travels after being squeezed out of the rubber and falls onto the carrier.
[0058] In summary, the present application includes at least one of the following beneficial technical effects:
[0059] 1. By adding zinc oxide and polyglycidyl ether polymer to the antistatic agent, the polyglycidyl ether polymer can react with active groups such as hydroxyl and carboxyl on the polyamide hard segment or polyether segment. On the one hand, a relatively complex cross-linking network is introduced in the polyether soft segment to obtain good mechanical strength. On the other hand, the cross-linking network of the polyether soft segment is connected to the end group of the polyamide hard segment. Although the reaction consumes the hydrophilic active groups, the reaction process also reintroduces the hydrophilic hydroxyl groups. Therefore, the cross-linking network structure of the soft segment cooperates with the ions of the zinc salt to form a more complete conductive network, which improves the mechanical strength of the antistatic agent and is accompanied by the improvement of the antistatic performance. At the same time, the present application is prepared into a special multi-microporous sheet structure by stretching and orientation before granulation. Although it will cause the mechanical strength of the antistatic agent to decrease, it can make the blended material (such as PA66) have higher mechanical strength and antistatic performance.
[0060] 2. By controlling the porosity of the antistatic agent, the length and short diameter of the surface stretching holes, and the hardness, on the one hand, it is ensured that the antistatic agent has good disentanglement and dispersion after mixing with the material to improve the mechanical strength. On the other hand, the highly oriented molecular chains are more likely to form an interconnected conductive network after dispersion to improve the antistatic ability. It is particularly important to note that the increase in the size of the pore structure leads to a decrease in the strength of the antistatic agent (such as from 80D to 70D), which can make the blended material have higher mechanical strength, which is quite unexpected.
[0061] 3. By controlling the preparation process of the antistatic agent, in particular, controlling the reaction degree of the polycaprolactam prepolymer to be no more than 700°C·h during the preparation, the polymerization degree of the polycaprolactam prepolymer is adjusted to be not too high, which can make the final antistatic agent have better mechanical strength and antistatic properties; further, in the polymerization step, a special two-step low-temperature-high-temperature reaction method is adopted. After the polyglycidyl ether polymer is added, the reaction temperature is increased to cause the ether bond of the polyether soft segment to break, which is generally undesirable, and the strength and antistatic properties of the polyether soft segment are improved.
[0062] 4. By further controlling the addition of a slightly excessive amount of zinc oxide, the antistatic agent can have not only a predictable better antistatic property, but also an unexpectedly higher mechanical strength.
[0063] 5. By further controlling the process parameters of step S5 extrusion granulation and stretching treatment, it can be ensured that when subjected to a stretching force, the molecular chains in the rubber have sufficient mobility to facilitate orientation, and the soft segment can be deformed or even broken into holes, thereby introducing a pore structure in the antistatic material, so that the final blended material has better mechanical strength and antistatic properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is a scanning electron microscope view of Example 1 of the present application.
[0065] Figure 2 It is a scanning electron microscope image of comparative example 3 of the present application. DETAILED DESCRIPTION
[0066] The following is combined with Figure 1-2 This application is described in further detail.
[0067] Example 1
[0068] The present application discloses a polyetheresteramide antistatic agent, the preparation process of which includes the following process steps:
[0069] S1. Preparation of zinc dicarboxylate: a dicarboxylic acid end-capping agent and zinc oxide are placed in a reaction container at a molar ratio of 1:2.35. In this embodiment, the dicarboxylic acid is adipic acid. Excess acetone is added as a solvent. The mixture is reacted at 35° C. for 50 min. The mixture is filtered, washed, and dried to obtain zinc dicarboxylate.
[0070] S2, preparation of polyether ester, adding a polyether compound to the prepared zinc dicarboxylate, controlling the molar ratio of zinc dicarboxylate to the polyether compound to be 1:1.15, in this embodiment, the polyether compound is specifically PEG-800, controlling the reaction temperature to be 165°C, and the reaction time to be 4 hours, to obtain a polyether ester with zinc.
[0071] S3, prepolymer preparation, caprolactam and a small amount of water are added to a reaction container. Specifically, the mass ratio of caprolactam to water is 20:1. Since water mainly plays the role of initiating the reaction, its amount has little effect on the final performance. It is only necessary to ensure that it is sufficient to initiate the reaction. Generally, it can be controlled to be not less than 50:1; the reaction is carried out in an inert gas atmosphere (specifically nitrogen) at a reaction temperature of 210°C, and the reaction degree is controlled to be no more than 700°C·h, specifically 630°C·h in this embodiment, to obtain a polycaprolactam prepolymer.
[0072] S4, polymerization, the polyether ester and polycaprolactam prepolymer prepared in step S2 and step S3 are mixed in a mass ratio of 0.25:1, first reacted for 1.5 hours under an inert gas atmosphere (specifically nitrogen) at 220°C, and then the polyglycidyl ether polymer is added, the added mass of the polyglycidyl ether is 0.3 times the mass of the added amount of the polyether ester. In this embodiment, the polyglycidyl ether is specifically polyethylene glycol diglycidyl ether, and the mixture is evacuated and heated to 260°C, and the reaction is continued for 2.5 hours to obtain a block polymer.
[0073] S5, extrusion granulation, specifically includes the following process steps:
[0074] S51, extrusion, mixing the block polymer obtained in step S4 with NMP to obtain a rubber material, and controlling the solid content to be 12.5wt%, controlling the temperature of the rubber material to be 90°C, and then extruding it onto a carrier. When extruding the rubber material, the distance between the rubber material extrusion port and the carrier is 3.5cm, and the speed of the carrier is greater than the extrusion speed of the rubber material. Specifically, the speed of the carrier is 2.5 times the extrusion speed of the rubber material. Then, the rubber material on the carrier is dried and solidified to obtain a rubber strip, and the drying temperature is controlled to be 15°C lower than the temperature of the rubber material;
[0075] S52, stretching treatment, stretching the rubber strip by 1.75 times at 35°C, and then heat treating it at 80°C for 45 minutes. After the heat treatment, cooling and pelletizing are completed to obtain a sheet-like antistatic agent with stretching holes. For details, see the attached manual. Figure 1 .
[0076] Embodiment 2-9
[0077] The main difference between Example 2-9 and Example 1 is that the preparation process of the antistatic agent is adjusted. Generally speaking, Examples 2-3 adjust various process parameters; Examples 4-6 mainly adjust the stretching process parameters in step S52; Example 7 mainly adjusts the process in step S4, appropriately increasing the amount of polyether soft segment and polyglycidyl ether; Example 8 mainly controls the amount of zinc oxide added to ensure that it is not excessive; Example 9 mainly controls the temperature of the rubber compound during extrusion and the distance between the rubber compound and the carrier in step S51.
[0078] See the table below for details:
[0079]
[0080]
[0081] Comparative Example
[0082] Comparative Example 1
[0083] The main difference between Comparative Example 1 and Example 1 is that no polyglycidyl ether is added when preparing the antistatic agent. Specifically, in step S4, the two-step low-temperature-high-temperature reaction method is not adopted, but a one-step low-temperature reaction method is directly adopted. The reaction temperature is still controlled at 220°C and the reaction time is controlled at 4h. The other process parameters are the same as those in Example 1 and are not repeated here.
[0084] Comparative Example 2
[0085] The main difference between Comparative Example 2 and Example 1 is that zinc oxide is not added when preparing the antistatic agent. Specifically, compared with Example 1, step S1 is cancelled, and the process starts directly from step S2. The other process parameters are the same as those in Example 1 and are not repeated here.
[0086] Comparative Example 3
[0087] The main difference between Comparative Example 3 and Example 1 is that, in the extrusion granulation step, no stretching process is used. Specifically, in Comparative Example 3, the block polymer obtained in step S4 is directly extruded and pelletized in a twin-screw extruder. The final antistatic agent is cylindrical / olive-shaped, and the antistatic agent has a dense structure without a porous structure. For details, see the attached specification. Figure 2 .
[0088] Performance Testing
[0089] Test specimen preparation
[0090] The polyetheresteramide antistatic agent prepared in each embodiment or comparative example was blended with commercially available PA6 (Sinopec Baling PA6BL3240 PA6), and the addition amount of the antistatic agent was controlled to be 5wt%, and then dried at 60°C for 12h, and pellets were obtained by extrusion through a twin-screw extruder. The extruder temperature was set to 230°C, 240°C and 230°C. For ease of testing, the test specimens were directly extruded to obtain pellets.
[0091] 1. Mechanical strength
[0092] With reference to the provisions of GB / T 2411-2018 Determination of indentation hardness (Shore hardness) of plastics and hard rubber using a hardness tester, the Shore hardness (D) of the antistatic agent prepared in each embodiment and comparative example, and the test specimen prepared above were tested respectively.
[0093] 2. Antistatic performance
[0094] The antistatic performance of the antistatic agent shall be based on the antistatic performance demonstrated by the test specimen. Specifically, refer to the provisions of GB / T31838.3-2019 Test requirements for surface resistance and surface resistivity of solid insulating materials to test the surface resistivity of each test specimen.
[0095] 3. Morphological parameters
[0096] The porosity of the antistatic agent is tested according to the relevant provisions in GB T 21650.1-2008 Determination of pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method Part 1 - Mercury intrusion method.
[0097] The pore size related parameters are obtained by magnifying the surface of the antistatic agent (SEM image) and by manual measurement or automatic measurement by software (image J).
[0098] The test results of various morphological parameters and Shore hardness (D) data of the antistatic agent are recorded in the following table:
[0099] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Porosity (%) 21.3 29.7 10.4 7.5 36.8 18.9 23.9 22.3 19.8 Hole length to diameter ratio 3.1 2.1 3.9 5.6 1.4 3.3 3.6 2.8 2.9 Shore D hardness 59D 42D 78D 84D 32D 69D 52D 53D 54D Hole length (nm) 203 295 102 84 377 184 452 214 186 Hole area ratio (%) 40.2 49.5 31.1 22.3 58.6 38.8 59.7 43.2 38.5
[0100] The test results of the hardness and antistatic performance of the test specimens are recorded in the following table:
[0101]
[0102] It should be noted that, since the resistance of the test strips in Comparative Examples 1-3 was relatively large and the antistatic performance was relatively poor, no further tests were performed on the corresponding antistatic agents.
[0103] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A polyetheresteramide antistatic agent, characterized in that: The antistatic agent has a polyamide hard segment and a polyether soft segment. The raw materials for preparing the antistatic agent include zinc oxide and a polyglycidyl ether polymer. The polyglycidyl ether polymer is one of polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, and glycerol triglycidyl ether, or a mixture of at least two of them. The antistatic agent is in a flake shape and has a microporous structure. The antistatic agent is stretched and oriented before being granulated.
2. A polyetheresteramide antistatic agent according to claim 1, characterized in that: The porosity of the antistatic agent is 10-30%, and the Shore hardness of the antistatic agent is 40-80D.
3. A polyetheresteramide antistatic agent according to claim 2, characterized in that: The surface of the antistatic agent has stretching holes, the stretching holes are in the shape of long strips, the long diameter of the stretching holes is 2-4 times the short diameter, and the Shore hardness of the antistatic agent is 50-70D.
4. A polyetheresteramide antistatic agent according to claim 3, characterized in that: The average major diameter of the stretching holes is 100-300 nm, and the area of the stretching holes accounts for 30-50%.
5. The method for preparing the polyetheresteramide antistatic agent according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: S1, preparation of zinc dicarboxylate, placing a dicarboxylic acid end-capping agent and zinc oxide in a reaction vessel, adding excess acetone as a solvent, reacting at a temperature of 30-40° C. for 40-60 minutes, filtering, washing, and drying to obtain zinc dicarboxylate salt; S2, preparation of polyether ester, adding a polyether compound to the prepared zinc dicarboxylate, controlling the reaction temperature to 160-170° C., and the reaction time to 3-5 h, to obtain a polyether ester with zinc; S3, prepolymer preparation, caprolactam and water are added into a reaction container, reacted in an inert gas atmosphere, the reaction temperature is 200-220°C, and the reaction rate is controlled to be no more than 700°C·h, to obtain a polycaprolactam prepolymer; S4, polymerization, mixing the polyether ester and polycaprolactam prepolymer prepared in step S2 and step S3, first reacting for 1-2 hours under an inert gas atmosphere at 210-230° C., then adding the polyglycidyl ether polymer, evacuating the mixture and heating the mixture to 255-265° C., and continuing the reaction for 2-3 hours to obtain a block polymer; S5, extrusion granulation, mixing the block polymer obtained in step S4 with NMP to obtain a rubber material, extruding it onto a carrier, the speed of the carrier being greater than the extrusion speed of the rubber material, then drying and curing the rubber material on the carrier to obtain a rubber strip, stretching the rubber strip and pelletizing it to obtain a sheet-like antistatic agent with stretching holes distributed therein.
6. The method for preparing the polyetheresteramide antistatic agent according to claim 5, characterized in that: In the step S4, the mass ratio of polyether ester to polycaprolactam prepolymer is 0.2-0.3:1; and the added amount of the polyglycidyl ether polymer is 0.2-0.4 times the added amount of the polyether ester.
7. The method for preparing the polyetheresteramide antistatic agent according to claim 5, characterized in that: In the step S1, the ratio of the amount of zinc oxide added to the amount of dicarboxylic acid end-capping agent added is controlled to be a molar ratio of 2.2-2.5:1; the dicarboxylic acid end-capping agent is selected from one of oxalic acid, adipic acid, sebacic acid, and suberic acid, or a mixture of at least two of them.
8. The method for preparing the polyetheresteramide antistatic agent according to claim 5, characterized in that: In the step S2, the molar ratio of zinc dicarboxylate to the polyether compound is 1:1.1-1.2; the polyether compound is one of polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol, or a mixture of at least two of them.
9. The method for preparing the polyetheresteramide antistatic agent according to claim 5, characterized in that: The step S5 specifically includes the following steps: S51, extrusion, mixing the block polymer obtained in step S4 with NMP to obtain a rubber material, and controlling the solid content to be 10-15wt%, controlling the temperature of the rubber material to be 80-100°C, and then extruding it onto a carrier, wherein the speed of the carrier is greater than the extrusion speed of the rubber material, and then drying and curing the rubber material on the carrier to obtain a rubber strip; S52, stretching treatment, stretching the rubber strip by 1.5-2 times at 30-40°C, and then heat treating it at 70-90°C for 30-60min. After the heat treatment, cooling and pelletizing are performed to obtain a sheet-like antistatic agent with stretching holes distributed therein.
10. The method for preparing a polyetheresteramide antistatic agent according to claim 9, characterized in that: In the step S51, the distance between the rubber extrusion port and the carrier is 2-5 cm, the speed of the carrier is 2-3 times the rubber extrusion speed, and the drying temperature is 10-20° C. lower than the temperature of the rubber.
Citation Information
Patent Citations
Preparation of zinc-containing polyether ester amides
CN101348566A
Composite two-way stretch light reflex polyester film and fabrication method thereof
CN103029391A